Green Synthsis dan Karakterisasi Nanopartikel Tembaga dengan Ekstrak Daun Gambir (Uncaria Gambir Roxb) untuk DYE Sensitized Solar Cell - Wargiyana, Sarah; Mardiansyah, Dedi; Puryanti, Dwi (Jurnal Fisika Unand, 2025)
Research has been conducted on Green Synthesis of copper nanoparticles using gambir leaf extract (Uncaria gambir Roxb) for Dye Sensitized Solar Cell. This study aims to determine the effect of the comparison of molar ratio variations (Cu(NO₃)₂) with gambir leaf extract through green synthesis of copper nanoparticles and I-V test of DSSC produced from copper nanoparticles through green synthesis. Sample preparation was carried out using the green synthesis method with the ratio of gambier leaf extract to (Cu(NO₃)₂) in sample variations of 1:1, 1:2, 1:3, 1:4 and 1:5. Copper nanoparticles were characterized using UV-Vis spectroscopy to determine the absorbance value and energy band gap and DSSC measured using a simple I-V test. UV-Vis spectrophotometer results on copper nanoparticles showed absorbance peaks in the 377 nm - 396 nm wavelength range, and obtained energy band gap values ranging from 2.84-2.91 eV. The resulting copper nanoparticles are round to elongated, due to the phenomenon of aggregation between particles. The efficiency obtained from DDSC is 4.26% and the FF value is 0.56.